INTERNATIONAL COMMUNITY DEVELOPMENT PRACTICE. - McConnell, Charlie; Daniel Muia, Daniel; Clarke, Anna. ([Place of publication not identified] : ROUTLEDGE, 2021)
International Community Development Practice provides readers with practice-based examples of good community development, demonstrating its value for strengthening people power and improving the effectiveness of development agencies, whether these be governmental, non-governmental or private sector. The chapters focus upon the making of the community development profession and the eight core competences required of the professional practitioner, as outlined by the International Association for Community Development (IACD), whatever their job title or host agency, in order to be able to undertake community development. These are concerned with the ability of the practitioner to: Put ethics and values into practice Engage with communities Ensure participatory planning Organize for change Support learning for change Promote diversity and inclusion Build leadership and infrastructure Develop and improve policy and practice From a policy perspective, the book will reassert the role of community development approaches as related to a wide variety of global challenges, including poverty amelioration, climate change, human rights, peace building and social, environmental, political and economic development. From a practice perspective, the book will reassert the importance of high levels of professional competence building upon decades of experience in the field around the world by development practitioners working in community work, social work, health, adult education, environmental protection, local economic development, urban design, cultural work and other disciplines concerned to support effective community development.
Keywords: Community development; ARCHITECTURE / Urban & Land Use Planning; POLITICAL SCIENCE / Public Policy / Social Policy; SOCIAL SCIENCE / Sociology / Urban